Modeling Integible Organizational Capital and Value Creation: The Case of Large Unlisted Moroccan Companies - Allouch, Faissal; Hafiane, Mohammed Amine (Business Perspective Review, 2022)
Purpose: Aim of this study is to investigate the relationships between the components of intangible organizational capital and value creation for unlisted Moroccan firms. Methods: A conceptual model was used to establish the relationship between the components of organizational capital and value creation for large Moroccan firms. The study used a structured questionnaire to collect data from managers of 176 large firms. We used structural equation modeling through AMOS software to test the relationships between the different variables in our model. Results: The study shows that organizational capital has a non-significant positive effect on value creation. This demonstrates that the efforts of the large firm have not been able to codify tacit knowledge and further improve organizational capital. Implications: The lack of organizational influence on value creation may signal that many firms prefer to invest heavily in physical capital without providing an adequate organizational structure. As a result, organizational capital deteriorates and leads to a lowering of the overall performance of intangible capital in addition to the value created for the company. The development of strong organizational capital can help to build an organizational culture to ensure that employees are able to innovate and deploy their know-how and experience for the benefit of the organization. Limitations: We still do not know how organizational capital changes over time. Therefore, a qualitative longitudinal study is recommended or a content analysis of companies’ annual reports.